(untitled) (Journal of Music Research Online, 2022)
An analysis of the chansons of Gilles Binchois used the graphical multivariate statistical technique of multidimensional scaling to quantitatively evaluate a carefully selected set of musical variables associated with the early fifteenth-century chanson repertory. The variables used in the analysis acknowledged that the superius and tenor voices of an early fifteenth-century chanson create a self- sufficient duet that forms the contrapuntal and harmonic core of the work and that this two-part contrapuntal framework (the Gerüstsatz) is enriched by a subordinate contratenor voice that makes an essential contribution to the overall musical texture. The findings indicated that this analytical framework was able to (i) resolve conflicting manuscript ascriptions, discover incorrect ones, and verify scholarly attributions of songs to Binchois, (ii) divide his complete secular output into four style periods approximately 8 to 10 years in length, (iii) date individual songs and manuscripts to within an accuracy of approximately plus or minus two years by mapping biographical data onto the results, and (iv) confirm and clarify the findings of previous manuscript studies. The internal consistency of the findings and their remarkable degree of agreement with the musicological literature strongly suggests that they could be used as a basis for future research and that the analytical framework could be applied to other repertories or composers whose works utilise a similar two-part contrapuntal core.